2007
DOI: 10.5006/1.3278390
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Performance of Concrete Cylinder Piles

Abstract: Concrete cylinder piles produced by a centrifugally cast, vibrated, roller-compacted process have shown promising corrosion resistance in marine environments. Three bridges in the Florida panhandle with ~40 years in aggressive marine service and one newly constructed marine bridge utilizing concrete cylinder piles were examined. Examination of the older marine bridges showed minimal corrosion distress despite low design concrete cover over the steel hoop reinforcement (2-4 cm). Typical concrete distress includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…This zone often is considered one of the most severe exposure conditions for corrosion of reinforcement in reinforced concrete structures (Richardson [2002]) as illustrated by the examples given by Gjorv (2009) and Angst et al (2012). However there are other cases where reinforced concrete structures have lasted for long periods of time even in the tidal and immersed zones (Lau et al, [2007]; Gjorv [2009]).…”
Section: Present Investigationsmentioning
confidence: 99%
“…This zone often is considered one of the most severe exposure conditions for corrosion of reinforcement in reinforced concrete structures (Richardson [2002]) as illustrated by the examples given by Gjorv (2009) and Angst et al (2012). However there are other cases where reinforced concrete structures have lasted for long periods of time even in the tidal and immersed zones (Lau et al, [2007]; Gjorv [2009]).…”
Section: Present Investigationsmentioning
confidence: 99%
“…2 Some isolated cases have been reported of no apparent occurrence of corrosion even after long exposure periods 3 even in normally highly aggressive environments. 4 On the other hand, there is also evidence of corrosion initiation even after relatively short periods of exposure. Moreover, laboratory experimental evidence has shown that although corrosion initiation can occur quite early, there may not be continued active corrosion until much later.…”
Section: Introductionmentioning
confidence: 97%
“…5,6 For marine environments the chlorides present in seawater usually are considered as the cause of reinforcement corrosion. 2 Despite some evidence to the contrary, 4 it is also accepted that durable reinforced concretes for these environments require considerable amounts of concrete cover to the reinforcement and high-density (quality) concretes to slow down the inward diffusion of chlorides from the surrounding environment (and by implication the loss of hydroxides to the external environment). Admixtures have been advocated widely as appropriate to creating less permeable concretes for the same purpose.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In extended systems the length of the initiation and propagation stages may change from point to point due to spatial variability of the model parameters, and treatments including appropriate statistical distributions of those parameters have been presented [7][8][9][10][11] . Spatial variability in C T due to different local conditions or to inherent dispersion of that parameter [12][13][14] has been introduced as well, leading to a more realistic representation of the development of corrosion in actual structures. However, those treatments tend to neglect coupling between the initiation and propagation stages of nearby regions, especially pertaining the effect of that coupling on the value of C T .…”
Section: Introductionmentioning
confidence: 99%